Continuous wireless pre‐ and postoperative vital sign monitoring reveal new, severe desaturations after vascular surgery. Issue 1 (1st November 2022) - Mølgaard, Jesper; Rasmussen, Søren Straarup; Eiberg, Jonas; Sørensen, Helge Bjarup Dissing; Meyhoff, Christian Sylvest; Aasvang, Eske Kvanner
Abstract: Objectives: Postoperative deviating physiologic values (vital signs) may represent postoperative stress or emerging complications. But they can also reflect chronic preoperative values. Distinguishing between the two circumstances may influence the utility of using vital signs in patient monitoring. Thus, we aimed to describe the occurrence of vital sign deviations before and after major vascular surgery, hypothesising that preoperative vital sign deviations were longer in duration postoperatively. Methods: In this prospective observational study, arterial vascular patients were continuously monitored wirelessly ‐ from the day before until 5 days after surgery. Recorded values were: heart rate, respiration rate, peripheral arterial oxygen saturation (SpO2 ) and blood pressure. The outcomes were 1. cumulative duration of SpO2  < 85% / 24 h, and 2. cumulative duration per 24 h of vital sign deviations. Results: Forty patients were included with a median monitoring time of 21 h preoperatively and 42 h postoperatively. The median duration of SpO2  < 85% preoperatively was 14.4 min/24 h whereas it was 28.0 min/24 h during day 0 in the ward ( p  = .09), and 16.8 min/24 h on day 1 in the ward ( p  = 0.61). Cumulative duration of SpO2  < 80% was significantly longer on day 0 in the ward 2.4 min/24 h (IQR 0.0–4.6) versus 6.7 min/24 h (IQR 1.8–16.2) p  = 0.01. Conclusion: Deviating physiology is common in patients before and after vascular surgery. A longer duration of severe desaturation was found on the first postoperative day in the ward compared to preoperatively, whereas moderate desaturations were reflected in postoperative desaturations. Cumulative duration outside thresholds is, in some cases, exacerbated after surgery.